FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR - Antonius Enrico, Virainy (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to know the effect of capital structure, firm size, asset tangibility, profitability and age of firm against financial distress on manufacturing company listed in BEI from 2015-2017. This research used 198 observations that were selected using purposive sampling methodin three years. This research uses EVIEWS software version 10 to analyse the hypothesis. The result for this research showed that there is a positive effect of capital structure on financial distress and there is negative effect between firm size, asset tangibility and profitability on financial distress. However, age of firm did not have any effect on financial distress.